Perlindungan Data Pribadi Klien pada Era Digital: Harmonisasi Regulasi Kenotariatan dan Hukum Perlindungan Data Pribadi - Fiona; Rizqiyah, Nazilatur (Magister Kenotariatan Universitas Surabaya, 2025)
In line with the rapid advancement of technology in the digital era, notaries have also begun using technological tools such as computers to create deeds. Nowadays, notaries face challenges in maintaining the security of their clients' data storage from digital threats such as computer viruses, data breaches and modifications, and even misuse of electronic signatures. Furthermore, personal electronic data is also vulnerable to hacking by irresponsible parties. This research aims to understand the regulation of personal data protection in Indonesia, particularly regarding the rights and obligations of notaries in managing their clients' data, as well as the legal-political relation of notarial regulations in ensuring the protection of clients' data, as viewed from the Notary Law. The research method used by the author is a normative juridical method through literature studies. In the era of information technology development, personal data protection becomes very important, especially in notarial practices involving legal documents that are private and sensitive. In addition to the Personal Data Protection Law, the Notary Law is also expected to provide a legal foundation to maintain the confidentiality and security of notary clients' data. Therefore, synchronization between the Notary Law and Personal Data Protection Law have its urgency, although both regulations have the same objective to protect client’s data, there is a need to synchronize them so that there is no overlap in their implementation.